PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH:KAJIAN ASPEK KEBAHASAAN - Syamsul Ghufron (MEDIA DIDAKTIKA, 2019)
Linguistic aspects of learning Indonesian in one curriculum with another curriculum experiencing dynamics. In the 1975 curriculum, linguistic aspects are taught in a separate (separate) manner. In the 1984 curriculum, linguistic aspects are contained in the structure learning unit in each chapter. In the 1994 and 1999 curriculums, linguistic aspects are still contained in the structure contained in the appendix. In 2004, 2006 and 2013 curriculum, linguistic aspects are not explicitly listed. From the study of linguistic aspects in each period of curriculum change, it appears that linguistic aspects must still be taught by the teacher even though they are not explicitly listed in the curriculum. This is based on the fact that the communicative approach aims that students have communicative competencies, one of which is linguistic or grammatical competence.